2011
DOI: 10.1111/j.1478-3231.2011.02528.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating apoptotic and necrotic cell death markers in patients with acute liver injury

Abstract: Plasma nucleosomes are significantly elevated following acute liver injury. Neither apoptotic nor necrotic cell death markers accurately predict survival following paracetamol-induced hepatotoxicity, suggesting that the extent and type of cell death play a limited role in determining outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 46 publications
1
68
1
Order By: Relevance
“…28,29 HMGB1, however, appears to have a role not only in infection and inflammation response but also in the pathological effects of many diseases, including rheumatoid arthritis, sepsis and acute liver injury and failure as well as viral infectious diseases. 16,17,30,31 It was observed that, when compared with negative controls, the plasma of HIV-1-infected patients contains higher HMGB1 concentrations, which can be correlated to the viral load. 19,32 In the case of West Nile Virus (WNV), depending on the viral dose, the infected cells undergo necrosis, and the concomitant release of HMGB1 contributes to the disease pathology.…”
Section: Discussionmentioning
confidence: 96%
“…28,29 HMGB1, however, appears to have a role not only in infection and inflammation response but also in the pathological effects of many diseases, including rheumatoid arthritis, sepsis and acute liver injury and failure as well as viral infectious diseases. 16,17,30,31 It was observed that, when compared with negative controls, the plasma of HIV-1-infected patients contains higher HMGB1 concentrations, which can be correlated to the viral load. 19,32 In the case of West Nile Virus (WNV), depending on the viral dose, the infected cells undergo necrosis, and the concomitant release of HMGB1 contributes to the disease pathology.…”
Section: Discussionmentioning
confidence: 96%
“…protein, a marker for necrosis 100,101 , in the supernatant of cells treated with higher concentrations of salinomycin. We further explored the mechanism of salinomycin-induced robust cell death under starvation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Although apoptosis is not the predominant pathway of cell death in APAP-induced liver injury, in studies of circulating cell death markers it has been shown increased necrosis and apoptosis-related keratin fragments in the blood of patients with APAP liver injury, and also lower levels of apoptotic keratin fragments have been observed in patients that survived, suggesting that if apoptosis occurs more readily this might be ''protective'' (Antoine et al, 2012;Bechmann et al, 2010;Craig et al, 2011;Volkmann et al, 2008). Ongoing cell death via necrosis and apoptosis in the livers removed during liver transplantation has also been reported (McGregor et al, 2003).…”
Section: Paracetamol-induced Liver Injurymentioning
confidence: 97%